A Case Study of Regional Sport Organization Development in Triathlon - Andrew J. Martin; Andrea N. Eagleman; Petr Pancoska (Journal of Applied Sports Management, 2014)
The current qualitative case study examined how a Regional Sport Organization (RSO) in New Zealand dealt with macro and micro environmental pressures in the development and evolution of increasing participation in the sport of triathlon over a 15-year period. Organizers managed a total participation increase from 300 adult participants in 1999 to close to 1,200 in 2012–13. An increase in child participants from 300 in 2004 to 3,400 in 2012–13 also took place. Archives of the results of the respective adult and children’s series of triathlon events from 1998–2013 were analyzed along with the environmental pressures. The findings indicated that informal and formal organizational responses to internal and external pressures directly or indirectly assisted in increasing sport participation of adults and children. These responses involved new events targeting different groups and periodic adaptive organizational infrastructure review/change. Implications of the research included the highlighted importance of ongoing sport product changes and enhancements and the use of formal internal and external review processes, such as the Organization Development Tool, for community or regional sports to support increased physical activity and participation.
Keywords: activity; participation; triathlon; community; organization